A Curvilinear-Path Umbrella Sampling Approach to Characterizing the Interactions Between Rapamycin and Three FKBP12 Variants - Joshi, Dhananjay C.; Gosse, Charlie; Huang, Shu-Yu; Lin, Jung-Hsin (Frontiers in Molecular Biosciences, 2022)
Rapamycin is a macrolide used as immunosuppressant that exhibits anti-proliferative properties through inhibiting the mTOR kinase. In fact, the drug first associate with the FKBP12 enzyme before interacting with its. Despite of the availability of structural and thermodynamic information on the FKBP12•rapamycin interaction, our energetic and mechanistic understanding is still incomplete. We recently reported a multiple-walker umbrella sampling simulation approach to characterizing the protein•protein interaction energetics along curvilinear paths. In the present paper, we extend our investigations to a protein•small molecule duo, the FKBP12•rapamycin complex. We estimate the binding free energies of rapamycin with wild-type FKBP12 and two mutants in which a hydrogen bond was removed, D37V and Y82F. Furthermore, the underlying mechanistic details are analyzed. The calculated standard free energies of binding agree well with the experimental data, and the roles of the hydrogen bonds are shown to be quite different in each of these two mutants. On one hand removing the carboxylate group of D37 strongly destabilize the association; on the other hand, the hydroxyl group of Y82 is nearly unnecessary for the stability of the complex because some nonconventional, cryptic, indirect interaction mechanisms seem to be at work.